APPLICATION OF DAILY MUFRODAT ADDITION PROGRAM IN IMPROVING THE ABILITY TO SPEAK ARABIC AT CLASS VII FEMALE STUDENTS AT IBNU MAS’UD FEMALE ISLAMIC BOARDING SCHOOL - Lutifyah, Lutfiyah Aini (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Learning Arabic at Pondok Pesantren Ibnu Mas'ud has differences with learning Arabic at school. Arabic in Pondok Pesantren Ibn Mas'ud using the addition of mufrodat program in every night that will provide the output achieved by students. This study aims to determine the effectiveness of the application of daily mufrodat addition Program Class VII Pondok Pesantren Ibnu Mas'ud in improving the ability to speak Arabic actively. This study uses a qualitative approach by collecting data from observations, interviews, and documentation studies. The results showed that the addition of mufodat program at Pondok Pesantren Ibnu Mas'ud has been adjusted to the class level of the students. This Program was prepared by ustadzah from the language section which has an important role in improving the Arabic language skills of santriwati, especially in daily communication, through good mastery of mufrodat.